Religiosity, Emotional Intelligence, and Tawadhu in Postgraduate Students - Salma Saraswati Dias; Yola Tiaranita; Fuad Nashori (Psikologia : Jurnal Psikologi, 2017)
College students are those people who educate themselves in university, that makes them have more knowledge than other students. But unfortunately, the more knowledge they have, the more they like to brag about themselves. Many people with higher education degree tend to brag about themselves to others in order to get appreciation, acknowledgement and respect. Those behaviors are against Islamic value that teaches us to be humble to others. This humility is called tawadhu’ in Islam. The purpose of this research is to find out the effect of religiousity and emotional intelligence to tawadhu’ in post-graduate students of UII. The subject of this research are 117 post-graduate students of UII. Based on double-regression in SPSS version 16, there is a correlation between religiousity and emotional intelligence to tawadhu’ with signification value of 0,000 (p<0,05) and F score of 14,294.